TALIF measurements of hydrogen and deuterium surface loss probabilities on quartz in low pressure high density plasmas. (12th January 2021) - Yang, X; Kogut, D; Couëdel, L; Angot, T; Roubin, P; Faure, J-B; Cartry, G
Abstract: This article deals with surface loss on quartz of atomic hydrogen (H) and its isotope deuterium (D) in a low-pressure (10 Pa) pulsed inductively coupled plasma. The atomic temporal decay in the post discharge is measured by two-photon absorption laser-induced fluorescence (TALIF). From the loss rate, the atomic surface loss probability is determined. In pure hydrogen or pure deuterium gas, no isotopic effect on surface kinetics has been observed and the surface loss probabilities of H and D were found to be almost identical and equal to ∼1.8%. However, despite the lack of difference in surface loss probability, a net isotopic effect on surface loss rate due to the mass difference between the isotopes is measured. Hydrogen atoms diffuse faster and have higher flux to the plasma chamber walls than deuterium atoms. Hydrogen atoms are therefore lost at higher rate than deuterium atoms. Based on the observed isotopic difference and on the comparison between H and D TALIF signals, the isotopic effects on H and D atom production are discussed.